FAKTOR-FAKTOR KUALITAS PEMERIKSAAN PADA PERUM BULOG DIVISI REGIONAL SUMATERA UTARA - Alpi, M. Firza (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2019)
This study aims to determine the influence of objectivity, competence, experience, integrity and accountability on the quality of examinations in the Perum Bulog, this study is also to know and analyze the influence of objectivity, competence, experience, integrity and accountability on the quality of examinations the Perum Bulog. This research uses associative research. The population used in this study were all employees of Internal Audit Perum Bulog. The sample taken in this study was 41 from census data on Perum Bulog. In this study data analysis models and techniques use a multiple linear regression approach. The results showed that the competency value showed a significance level of 0.001, Integrity showed a significance value of 0.009 and accountability of 0.003 where the three variables were smaller than 0.05 which partially had a significant effect on the Quality of Examination at the Perum Bulog. Other variable have no partial effect on the quality of the examination.